2018
DOI: 10.1002/jhet.3179
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Anticancer Activity Study of Novel Series of Substituted and Fused Coumarin Derivatives

Abstract: Various new substituted and fused coumarin analogues have been synthesized via different synthetic pathways. Among which are variable substituted coumarin derivatives bearing either biologically active side chains or rings at 5, 6, and 3 positions of the coumarin nucleus as indicated in compounds 10, 12, 13, 16–19, 21, 23–32, 38, and 42–45. In addition, different pyranocoumarin derivatives either substituted as in compounds 2, 3, and 6 or fused as compounds 33–36, pyranoxanthene analogues such as compounds 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Other surveys revealed that various synthesized bi‐heterocyclic derivatives containing both the imidazole and [1,2,4] triazole nuclei served as compounds of high biological potency . Our survey about the previously synthesized imidazo[1,2,4]triazole derivatives guided us to several derivatives that were reported as biologically active anticancer agents which fall in our field of interest concerning the synthesis of different heterocyclic molecules with anticancer activity …”
Section: Introductionmentioning
confidence: 81%
“…Other surveys revealed that various synthesized bi‐heterocyclic derivatives containing both the imidazole and [1,2,4] triazole nuclei served as compounds of high biological potency . Our survey about the previously synthesized imidazo[1,2,4]triazole derivatives guided us to several derivatives that were reported as biologically active anticancer agents which fall in our field of interest concerning the synthesis of different heterocyclic molecules with anticancer activity …”
Section: Introductionmentioning
confidence: 81%
“…The NMR spectra of compound 3 showed two D2O changeable singles at 8.3 and 8.4 ppm corresponding to NH and =NH, respectively. Basic catalyzed reaction of 1 with malononitrile afforded 9,11-diamino-12-(4-methoxyphenyl)-14,12H-benzo [5,6] chromeno[2,3-b]pyridin-10-carbonitrile (4). Interaction of compound 1 with carbon disulfide in dimethyl sulfoxide gave 9mercapto [2,3-d]pyrimidin-11-thione derivative (5) (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…However, there are other targets for anticancer activity among fused triazoles, such as hsp90 (Xu et al, 2016;Casale et al, 2014), kinase (Sun et al, 2019;Hou et al, 2019;Martínez-Gonzá lez et al, 2019), topoisomerase II (Ribeiro et al, 2019) and tubulin (Briguglio et al, 2017;Zaki et al, 2018). Interestingly, many studies have been devoted to s-triazolo [3,4-b][1,3,4]thiadiazines, which have been shown to have a wide spectrum of biological activity, including anticancer (LaPorte et al, 2016;Zhang et al, 2015;Hassan et al, 2018;Kamel & Megally Abdo, 2014;Khan et al, 2014), antimicrobial (Haggam, 2016;Almajan et al, 2010;Karthikeyan et al, 2008;Ghattas et al, 2012;El-Sayed & Asghar, 2014;Ghorab et al, 2000;Hassanien, 2003;Aggarwal et al, 2011;Ö zil et al, 2015) and anti-inflammatory (El Shehry et al, 2010;El-Serwy et al, 2013), while information on the biological profile of isomeric as-triazolo [5,1-b] [1,3,4]thiadiazine is limited. Some recent research has shown that spiro derivatives of as-triazolo [5,1-b] [1,3,4]thiadiazine can inhibit the growth of rhabdomyosarcoma (RD) tumour cells (Kalinina et al, 2015) and some compounds had a stimulating effect on the growth and development of plant seeds (Kalinina et al, 2018;Vysokova et al, 2019) and animal cells (Kalinina et al, 2015).…”
Section: Introductionmentioning
confidence: 99%